Faktor yang Berhubungan Dengan Muskuloskeletal Disorders (MSDs) Pada Pekerja Tenun Ulos di Kecamatan Siantar Selatan Kota Pematangsiantar Tahun 2016 - Muliati Muliati (FORUM ILMIAH KESEHATAN, 2020)
Research was conducted on ulos weaving workers in Siantar Selatan Subdistrict Pematangsiantar City to find out the factors that influence the complaints of Musculoskeletal Disorders (MSDs). Musculoskeletal Disorders (MSDs) generally occur due to occupational factors and individual factors (posture, length of work, workload, frequency, age, employment). This research is a quantitative research with cross sectional design, this research sample amounted to 30 people. The complaints of Musculoskeletal Disorders (MSDs) in workers was measured by using Nordic Body Map (NBM) and categorized into no pain, and sick. This study used Chi square test to see the relationship between independent and dependent variables and used multiple logistic regression test to find out which variables are most significant relate to dependent variable with Backward Stepwise method. The results showed that ulos weaving workers experienced the most pain complaints on the waist as many as 26 people (86.7%), the level of complaints at the waist most abundant in ulos weaving workers that category pain as many as 25 people (83.3%) and category did not hurt 5 people (16.7%). The result of statistical test shows that age (p value=0.919), work period (p value=0.020), work load (p value=0.431), body posture (p value=0.019), frequency (p value=0.873) (p value=0.314), which has a relationship to the complaints of Musculoskeletal Disorders (MSDs) is the working period p value=0.020 (p